Produktivitas Bongkar Muat Pelabuhan Dwikora Pontianak Kalimantan Barat - Ditya Amanda Pratiwi; Arfena Deah Lestari; Jasisca Meirany (Fakultas Teknik Universitas Pasifik Morotai, 2024)
Dwikora Port is the main port in West Kalimantan Province which functions to carry out Port service activities such as loading and unloading goods, both containers and non-containers. In 2022, the Kijing Terminal located in Mempawah began operations to help improve connectivity and expand accessibility to the West Kalimantan region. To find out this impact, an evaluation of loading and unloading productivity at Dwikora Port Pontianak needs to be carried out. In this study, loading and unloading, effective time and berthing time data for 2019-2022 were used from Pelindo Regional II Pontianak. The data processing process uses a quantitative descriptive method with the help of Microsoft Excel. From the formula B/S/H, T/S/H and ET/BT, the average B/S/H unloaded and loaded in 2019-2022 is 164,855 B/S/H and 161.50 B/S/H. The average T/S/H unloaded and loaded in 2019-2022 is 1,094.99 T/S/H and 531.92 T/S/H and ET/BT in 2019-2022 is 54%. The standard performance of loading and unloading productivity based on the Director General of Transportation in 2016 is 24 B/S/H, 24 T/S/H and 65%. The results of the analysis of loading and unloading productivity based on B/S/H, T/S/H in 2019-2022 were declared good and ET/BT in 2019-2022 were declared poor. Influencing factors are bad weather, the performance of loading and unloading equipment, operator or labor time, and the time the ship is moored.